The effect of a laser device on some biomechanical variables of the rotational phase in the achievement of 100 m freestyle swimming for the Iraqi team (16-18 years old) - Yahya, S. Z.; Abdul Rida, B. K.; Abdulkareem, O. W. (Scientific Journal of Sport and Performance, 2024)
The researchers have discovered weaknesses in the rotational phase of the 100-meter freestyle event, including a lack of proper movement direction and control of biomechanical variables necessary for swimmers to achieve high rotational accuracy, which leads to outperforming competitors. The objective of this study was to investigate the effect of using a laser device on improving the performance of the rotational phase among swimmers on the Iraqi national team. The experimental approach was conducted on a sample of 6 swimmers, representing 100% of the target population. The researchers concluded that the utilization of a proposed laser device in the rotational phase resulted in positive differences in biomechanical variables, contributing to the enhancement of swimmers' performance and increasing the horizontal distance achieved. Consequently, the researchers recommend the implementation of a laser device during the rotational phase to detect weaknesses and enhance strengths, thereby facilitating coaches in the development of swimmers.